Signalling mechanism in TRPM2-dependent copper- induced HT22 cell death - Rathakrishnan, Sharani; Hazanol, Iffa Nadhira; Dali, Mohd Haziq Izzazuddin; Sha’fie, Muhammad Syahreel Azhad; Ahmad, Syahida; Alitheen, Noorjahan Banu; Syed Mortadza, Sharifah Alawieyah (Hibiscus Publisher, 2023)
Copper (Cu) is one of the critical elements needed by the human body. However, this metal can cause cytotoxicity when present in excess amounts. In this study, we used HT22 hippocampus cells to examine the function of the Ca2+-permeable transient receptor melastatin 2 (TRPM2) channel in Cu-induced neuronal cell death and the underlying mechanisms. Immunocytochemistry, single-cell imaging, acridine orange/propidium iodide (AO/PI) cell death assay and immunofluorescence microscopy were applied to interpret the mechanisms involved in Cu-induced HT22 cell death. Treatment of 30-300 μM Cu induced an increase in the [Ca2+]i in HT22 cells. Further analysis indicates that Cu exposure induced substantial HT22 cell death. Such response on HT22 cells was significantly inhibited by 2-aminoethoxydiphenyl borate (2-APB) and N-(p-amylcinnamoyl)anthranilic acid (ACA), TRPM2 channel inhibitors. Furthermore, Cu-induced HT22 cell death was suppressed by pharmacologically inhibiting poly(ADPR) polymerase (PARP) using PJ-34 and DPQ. It is known that the activation of TRPM2 channel is via the increase of intracellular reactive oxygen species (ROS). A significant concentration-dependent increase in the generation of ROS was observed in HT22 following the treatment with 30-300 μM Cu. Additionally, Cu-induced HT22 cell death was ablated by inhibiting PKC using CTC, a PKC inhibitor and NADPH oxidase (NOX) using DPI, a NOX generic inhibitor and GKT137831, a NOX1/4-specific inhibitor. Overall, our present study provides evidence suggesting that PKC/NOX/ROS/PARP is an important signalling pathway in Cu-induced activation of the TRPM2 channel and increase in the [Ca2+]i which eventually results in the toxicity of HT22 cells. These results provide new insights into the mechanisms of neurological-associated Cu-induced diseases.